Study of electrostatic fields using Bessel functions - Khizirova, M.A.; Bisariyeva, ZH.B.; Iskakova, S.K. (Recent Contributions to Physics, 2015)
Electron - and ion-beam tubes are widely used in modern science and technology. Industrial and household TV, electron microscopes, particle accelerators, mass spectrometers of various modifications, electro-optical converters - this is not a complete list of applications of charged particle beams. These beams have unique technological capabilities and their field of application in recent years expanded rapidly. Tightly focused beams of charged particles are widely used in medicine, intensively studied the possibility of using accelerated ion beams to create a jet thrust, allowing the creation of spacecraft capable of flying at speeds close to the speed of light. Thus, the main objective is to obtain the electron optics using beams of charged particles under the influence of electric and magnetic fields of high electron or ion images. This problem is considered and studied the theory of focusing of charged particles. Why using a mathematical package MathCad for example axis symmetric electrostatic mirror obtained axial distribution of the Bessel function of the first kind for electrostatic potential distribution along the optical axis.